Hereditary Protein C Deficiency Associated with Mutations in Exon IX of the Protein C Gene - Doig, R G; Begley, C G; McGrath, K M (Thrombosis and Haemostasis, 1994)
This report describes five families with symptomatic hereditary protein C deficiency. Using a polymerase chain reaction (PCR)-based method, the entire coding sequence and intron-exon boundaries of the protein C gene was amplified from genomic DNA. In each family a single point mutation in the protein C gene was identified. Two unrelated families were found to share the same mutation, while the other three had different mutations. In the first two families with type I protein C deficiency the normal cytosine residue at nucleotide position 8551 in the protein C gene was replaced by thymidine leading to substitution of the normal proline residue at amino acid position 279 by leucine. In the third family with type I deficiency a previously undescribed mutation was identified. In this family the guanosine residue at position 8559 was replaced by adenosine (glycine 282 substituted by serine). In the fourth family, also with type I deficiency, guanosine 8589 was replaced by adenosine (glycine 292 substituted by serine). The fifth family had type II deficiency and in affected members cytosine 8769 was replaced by thymidine (arginine 352 substituted by tryptophan). All these mutations lead to amino acid substitutions in the serine protease domain of the mature protein. All were able to be confirmed by restriction enzyme analysis of PCR-derived DNA. In addition the novel mutation at nucleotide position 8559 was also demonstrable using single strand conformation polymorphism (SSCP) analysis of PCR-derived DNA. These mutations were likely examples of deamination of methylated cytosine occurring in cytosine-phosphate-guanosine (CpG) dinucleotide sequences. These findings confirm the genetic heterogeneity of hereditary protein C deficiency in these families.